2018
DOI: 10.1021/acs.jpcb.7b12229
|View full text |Cite
|
Sign up to set email alerts
|

Star Block-Copolymers in Shear Flow

Abstract: Star block-copolymers (SBCs) have been demonstrated to constitute self-assembling building blocks with specific softness, functionalization, shape, and flexibility. In this work, we study the behavior of an isolated SBC under a shear flow by means of particle-based multiscale simulations. We systematically analyze the conformational properties of low-functionality stars, as well as the formation of attractive patches on their corona as a function of the shear rate. We cover a wide range of system parameters, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 33 publications
2
27
1
Order By: Relevance
“…28 We have characterized the dependence of several observables of interest measuring the size, orientation and intrinsic viscosity, on the applied shear rate. The obtained power-laws have characteristic exponents that are clearly different from those found in other architectures (linear chains, rings, stars, dendrimers [28][29][30][31][32][33][34][35][36][37][38] ). Thus, SCNPs constitute a novel class of macromolecules with distinct response to shear.…”
Section: Introductioncontrasting
confidence: 68%
“…28 We have characterized the dependence of several observables of interest measuring the size, orientation and intrinsic viscosity, on the applied shear rate. The obtained power-laws have characteristic exponents that are clearly different from those found in other architectures (linear chains, rings, stars, dendrimers [28][29][30][31][32][33][34][35][36][37][38] ). Thus, SCNPs constitute a novel class of macromolecules with distinct response to shear.…”
Section: Introductioncontrasting
confidence: 68%
“…On the other opposite limit, at high α and λ (α 0.6 and λ 1.1), the macromolecule acquires cylindrical symmetry around its principal axis, since it self-assembles into dumbbell-like structures with one or two massive patches (Case 3). At intermediate values of α and λ, the SBCs form a number of patches that can break-up and/or merge as a consequence of shear (Case 2) [9][10][11]. These three tendencies can be also observed from the dynamical point of view, as displayed in Fig.…”
Section: Rotationalmentioning
confidence: 81%
“…We focus on the following three particular sets of parameters: { f , α, λ} = {12, 0.3, 1.0} (Case 1), {15, 0.5, 1.1} (Case 2) and {18, 0.7, 1.1} (Case 3). According to our previous study, these parameters represent the typical trends found in regard to the patchiness of the SBCs, namely, no patches are formed, several patches are formed having a small population, and few (one or two) bulky patches are formed [11]. For each run, a preparation cycle of 5 × 10 6 MD steps was executed in first place, which was long enough for the SBC to reach its stationary state and then, a production cycle of 1.5 × 10 7 MD steps took place.…”
Section: Multiparticle Collision Dynamics (Mpcd) and Molecular Dynamimentioning
confidence: 88%
See 2 more Smart Citations